2019
DOI: 10.1016/j.arth.2019.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Better Implant Positioning and Clinical Outcomes With a Morphometric Unicompartmental Knee Arthroplasty. Results of a Retrospective, Matched-Controlled Study

Abstract: Keywords:unicompartmental knee arthroplasty morphometric tibial tray implant positioning medial overhang tibial bone coverage a b s t r a c t Background: During medial unicompartmental knee arthroplasty (UKA), tibial tray implantation requires compromise between bone coverage and rotational position. It was hypothesized that morphometric tibial tray (MTT) would improve implant positioning and subsequently clinical outcomes as compared to symmetric tibial tray (STT). Methods: A total of 106 patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The anatomical differences between the medial and lateral tibial plateau are not taken into account. The use of a custom UKA or a morphometric implant [ 45 ] can be the solution. Patient-specific instruments can easily help with accurate cuts, avoiding too deep posterior cuts or undercutting of the spine [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The anatomical differences between the medial and lateral tibial plateau are not taken into account. The use of a custom UKA or a morphometric implant [ 45 ] can be the solution. Patient-specific instruments can easily help with accurate cuts, avoiding too deep posterior cuts or undercutting of the spine [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our study did not find a significant difference in the femoral rollback motion between preoperative and postoperative knees. The advantages of the morphometric implants in the UKA positioning have been described in a previous comparative study [ 30 ]. They allow to optimize the rotational-coverage ratio and the femoral fit, avoiding the compromises between size and positioning.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning that using different tibial trays in UKA has an impact on implant positioning. This was investigated by Escudier et al, and they found that using a morphometric tibial tray is better than using a symmetric tibial tray in terms of decreasing the rate of overhand and improving the short-term clinical outcomes at one-year follow-up [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Functional assessment of KSS, FKS, and ROF. morphometric tibial tray is better than using a symmetric tibial tray in terms of decreasing the rate of overhand and improving the short-term clinical outcomes at one-year follow-up [14].…”
Section: Radiologic Evaluation (Ap and Lateral Views)mentioning
confidence: 92%